Research on the influence of entertainment on consumer deep engagement in brand-hosted live streaming: The moderating effect of knowledge level and psychological ownership - Wang, Lingfei; Chen, Chun-Shuo (Edelweiss Applied Science and Technology, 2026)
With the rapid development of brand-hosted live streaming, the live commerce ecosystem has shifted from a super-streamer-dominated model to a more decentralized, brand-driven approach. Drawing on the Stimulus–Organism–Response (S-O-R) model and Brand Co-Creation Theory, this study aims to examine how entertainment in brand-hosted live streaming influences consumer deep engagement through immersive experience, while also testing the moderating roles of knowledge level and psychological ownership. A quantitative survey was conducted, yielding 544 valid responses, and multiple regression analysis was employed to test the proposed hypotheses. The findings indicate that entertainment has a significant positive effect on consumer deep engagement. Immersive experience plays a mediating role in this relationship. Moreover, knowledge level and psychological ownership significantly moderate the relevant pathways. This study extends the application of the S-O-R framework in the context of brand-hosted live streaming and provides practical implications for optimizing entertainment-oriented strategies to enhance consumer deep engagement.